Identify VO2 max levels in Malang United F.C Players Indonesian League 3 East Java Regional - Ghana Firsta Yosika (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2023)
Objective. The primary goal of this research is to evaluate and quantify the maximum oxygen uptake capacity (VO2 max) of the players from the renowned football club, Malang United FC. The players selected for this study are the ones who actively participate in the highly competitive East Java Regional Indonesian League 3. By analyzing their VO2 max endurance levels, we aim to gain a comprehensive understanding of their cardiovascular fitness and overall physical performance, which can potentially help the coaches and trainers to optimize their training regimes and improve the team's overall performance in the league. Material and Method. The research employed the Qualitative Descriptive method, with the research subjects consisting of 23 players from Malang United F.C. who are currently participating in the East Java Regional Indonesian League 3. The study utilized a multi-stage fitness test, also known as the bleep test, to measure the VO2 max of the research subjects. The data obtained from this study were analyzed using descriptive quantitative percentages. Result. According to the findings of the study, the average VO2 max level among the participants was determined to be within the range of good (40.80-55.70 ml/kg/minute). The analysis further revealed that out of the total 23 subjects, 1 individual was categorized as having a poor VO2 max level, 3 individuals had an adequate level, 12 individuals had a good level, and 7 individuals had a very good VO2 max level. Conclusion. Based on the research findings, it can be inferred that the football players of Malang United F.C. have a commendable average VO2 max level. VO2 max is a crucial factor in the game of football, and a good VO2 max can contribute significantly to achieving optimal results as a football player.